RDNA-09. RADIATION DRIVES THE EVOLUTION OF ORTHOTOPIC XENOGRAFTS INITIATED FROM GLIOBLASTOMA STEM-LIKE CELLS. (5th November 2018) - McAbee, Joseph; Rath, Barbara; Wu, Xiaolin; Camphausen, Kevin; Tofilon, Philip
Abstract: The clonal diversity and evolutionary dynamics inherent to GBMs is considered a major obstacle to effective treatment development. While studies have focused on temozolomide, a role for radiotherapy as a driver of GBM evolution has not been investigated. This study seeks to better understand the impact of radiotherapy, an important component of most treatment regimens, on GBM evolution. We intracranially implanted NSC11 and NSC20, CD133+ glioma stem-like cell lines, into nude mice. Bioluminescence imaging on day 21 post-implant confirmed the presence of tumor prior to randomization into control and radiotherapy groups (3x5Gy). Brain tumor xenografts were collected out to morbidity to assess morphological and histological changes following irradiation and to extract DNA for viral integration site analysis (VISA). Survival analysis demonstrates a significant survival advantage for mice undergoing radiotherapy (+31 days, NSC11; +36 days, NSC20). Gross examination at morbidity revealed brains bearing irradiated tumors contained tumor tissue that is more distinct, softer and more adherent, and more likely to efface olfactory bulb(s) than control tumor brains. H&E and SOX2 staining support these findings of a more infiltrative growth pattern in control tumors compared to irradiated tumors. VISA for NSC11 and NSC20 allowed for the examination of relative clonal diversity. Unsupervised hierarchical cluster analysis demonstrated a reduction in clonal diversity when transitioning from in vitro culture to in vivo conditions. Further reduction in clonal diversity is apparent when comparing control and irradiated tumors. To investigate whether the brain environment was necessary for the radiation-induced reduction in clonal diversity, NSC11 cells were irradiated in vitro and collected for VISA. Clonal diversity remained relatively consistent regardless of treatment. Our results demonstrate that radiation, in the context of the brain microenvironment, drives GBM evolution resulting in tumor morphology/histology modifications and tumor cell subpopulation selection. This process may have implications for treatment of recurrent GBM.